The fine art of the big talk how to win clients, deliver great presentations, and solve conflicts at work - Fine, Debra (New York Hyperion, 2008)
Makes recommendations for managing communication in business, from giving a negative performance appraisal to submitting a complaint to a service provider, in a guide that features strategies for tailoring discussions for a given audience and overcoming fear.
E.Gernale
Keywords: Business communication; Oral communication; Communication